Perbandingan makhraj huruf jīm dan qāf dalam lagu ‘حبّه جنّة’: kajian fonetik dialek mesir - Nuriyah, Afrizatun (Maliki Interdisciplinary Journal, 2025)
This study analyzes the articulation differences between the phonemes Jīm and Qāf in the song “Hubbuh Jannah” by Sherine Abdel Wahab, as a phonetic representation of the Egyptian Arabic dialect. The background of this research lies in the phonological shift of these sounds, which deviate from standard Arabic norms, particularly in the context of popular music. This research employs a qualitative descriptive approach using articulatory phonetic analysis. The data consist of selected lyrics containing the target phonemes, analyzed using Praat software to identify their articulatory features and acoustic properties. The results indicate that Jīm is realized as an affricate sound [ʒ] or [dʒ], while Qāf shifts to a glottal stop [ʔ] or is even omitted in certain contexts. These shifts reflect a distinctive phonetic characteristic of the Egyptian dialect, which tends to simplify posterior articulation. This study highlights the importance of phonetic analysis in understanding pronunciation variation across Arabic dialects and the role of music as a medium for maintaining and spreading dialectal features.